A Dictionary of Political Thought - Roger Scruton (Pan Reference, 1983)
This new edition takes stock of the revolutionary changes that have taken place since the dictionary was first published in 1982. 1790 entries cover every aspect of political thought providing an indispensable guide to the thought, the wisdom and the folly of modern politics by one of the most lucid philosophers of our time.